"Ustawy prawa polskiego najpotrzebniejsze, krótko z łacińskiego wybrane, na polski język przełożone" (1559) Jana Palczowskiego jako przykład popularnej kodyfikacji prywatnej w dawnej Polsce - Naworski, Zbigniew (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
A paper presents a private legal compendium by Jan Palczowski — the land judge for nobility from Zator, entitled Polish laws most needed, from Latin, shortly gathered, into Polish translated, published for the first time in 1559, reprinted a few times later on. Palczowski prepared his work because of the incorporation of the Duchy of Oświęcim and Zator into the Polish-Lithuanian Commonwealth; however, it gained vast popularity in the whole country. Compared to other similar compendiums, Palczowski’s Collection was quite extensive. Selected provisions reflected problems typical for the average nobleman — a wealthy proprietor of the land. The way Palczowski’s compendium was edited suited the readers’ expectations. It did not contain any new elements (generally considered damaging at the time) and was focused on commonly accepted and known privileges and statutes. It seems like the judge from Zator was perfectly aware of the Polish nobility’s attitudes, opinions, and expectations. Thanks to that, his work was adequate for the taste of many recipients.
Keywords: private codification; legal compendium; land judge for nobility; nobility of the Crown of Poland